ESTABLISHING ECONOMIC EMPOWERMENT SYSTEM THROUGH MOSQUE BASED COMMUNITY - Iqbal Imari; Adib Susilo; Mahendra Utama Cahya Ramadhan (Referensi Islamika: Jurnal Studi Islam, 2026)
This study is aimed to propose a holistic model for mosque-based economic empowerment, grounded in both theoretical foundations and practical applicability. A qualitative approach employs in this study with adopts a conceptual research method, focusing on the theoretical exploration and development of a comprehensive framework for mosque-based economic empowerment. Data in this study collected from secondary data of books, journals, and reports. A qualitative-Inductive analysis to synthesize existing literature and derive a conceptual framework which involves thematic Analysis which is the literature categorized into themes employed to analyze the data. The finding of this study shows that the Islamic Empowerment principles (justice, equity, participation, rewards, and mutual aid or ta’awun) and its dimension (faith, knowledge, and social activity) are in necessity to be integrated with mosque-based economic empowerment. The integration between this two concepts create a model are through 5 steps. By taking this steps into action mosque is not only become a ritual house but also a center of hope and opportunity, providing practical solutions to economic challenges and a home for everyone in needs. This study also has several limitations. For example, this study is a conceptual framework. An implementation of this concept and model is become a future agenda as suggestion. Moreover, the model that implemented in the future also able to be examine empirically to seek whether the model is suitable for different demographic and context. This study contributes by providing the model of mosque based economic empowerment which is based with Islamic economic empowerment through 5 steps namely, community needs assessment; resource mobilization; program development; implementation & monitoring; long-term sustainability & growth. By taking this steps into action mosque is not only become a ritual house but also a center of hope and opportunity, providing practical solutions to economic challenges and a home for everyone in needs.